Nitrile Hydratase Genes Are Present in Multiple Eukaryotic Supergroups - Marron, Alan O. (Public Library of Science, 2012)
BACKGROUND: Nitrile hydratases are enzymes involved in the conversion of nitrile-containing compounds into ammonia and organic acids. Although they are widespread in prokaryotes, nitrile hydratases have only been reported in two eukaryotes: the choanoflagellate Monosiga brevicollis and the stramenopile Aureococcus anophagefferens. The nitrile hydratase gene in M. brevicollis was believed to have arisen by lateral gene transfer from a prokaryote, and is a fusion of beta and alpha nitrile hydratase subunits. Only the alpha subunit has been reported in A. anophagefferens. METHODOLOGY/PRINCIPAL FINDINGS: Here we report the detection of nitrile hydratase genes in five eukaryotic supergroups: opisthokonts, amoebozoa, archaeplastids, CCTH and SAR. Beta-alpha subunit fusion genes are found in the choanoflagellates, ichthyosporeans, apusozoans, haptophytes, rhizarians and stramenopiles, and potentially also in the amoebozoans. An individual alpha subunit is found in a dinoflagellate and an individual beta subunit is found in a haptophyte. Phylogenetic analyses recover a clade of eukaryotic-type nitrile hydratases in the Opisthokonta, Amoebozoa, SAR and CCTH; this is supported by analyses of introns and gene architecture. Two nitrile hydratase sequences from an animal and a plant resolve in the prokaryotic nitrile hydratase clade. CONCLUSIONS/SIGNIFICANCE: The evidence presented here demonstrates that nitrile hydratase genes are present in multiple eukaryotic supergroups, suggesting that a subunit fusion gene was present in the last common ancestor of all eukaryotes. The absence of nitrile hydratase from several sequenced species indicates that subunits were lost in multiple eukaryotic taxa. The presence of nitrile hydratases in many other eukaryotic groups is unresolved due to insufficient data and taxon sampling. The retention and expression of the gene in distantly related eukaryotic species suggests that it plays an important metabolic role. The novel family of eukaryotic nitrile hydratases presented in this paper represents a promising candidate for research into their molecular biology and possible biotechnological applications.